Nanofiber Cellulose as New Generation Natural Materials for Biocomposite Filler - Asrofi, Mochamad; Pradiza, Revvan Rifada; Abduh, Muhammad; Junus, Salahuddin; Alahmadi, Mohammed (Green Engineering Society, 2024)
Cellulose, a ubiquitous and renewable biopolymer, has garnered significant attention for its potential in material applications. This overview highlights the properties and applications of cellulose nanofibers, a nanoscale form of cellulose with exceptional properties. Cellulose nanofiber exhibits high surface area-to-volume ratios, inherent crystallinity, and favorable mechanical properties. They can be extracted from various sources using chemical and mechanical treatments, including alkali treatment, bleaching, acid hydrolysis, and ultrasonication. These processes effectively reduce cellulose fibers to the nanoscale, enhancing their properties. Cellulose nanofiber has demonstrated significant potential as reinforcing agents in biocomposites, improving interfacial adhesion, homogeneity, and mechanical strength. Their applications extend to diverse sectors, including biomedicine, packaging, and 3D printing. In biomedicine, Cellulose nanofiber show promise in tissue engineering, drug delivery, and wound healing due to their biocompatibility. Their lightweight yet strong nature and biodegradability make them ideal for sustainable packaging solutions. Moreover, cellulose nanofiber serves as effective reinforcing agents in composites, enhancing the mechanical properties of polymers for applications in automotive and aerospace industries.